(untitled) (Bioagro, 2021)
In the horticultural zone of Quíbor, Lara state, Venezuela, the cultivation of onion with furrow irrigation has been applied as a conventional management system, although changes are currently being implemented in the agricultural production, that affect the soil, such as cropping of super sweet corn. The objective of this study was to compare, the soil quality under both production systems. The research was quasi-experimental in nature, with soil samplings at three different depths in each site. Soil quality was determined based on the level of degradation of 13 chemical, physical and biological attributes that had been selected as indicators in a previous work. Both the soil under the conventional system-super sweet corn and the conventional-onion system presented low quality in the studied strata, particularly because they shared high degradation in the ratios of Ca/organic matter and macro/microporosity, as well as in microbial biomass, although they differed in indicators such as P content, C/N and Ca/Mg ratios, total porosity and the metabolic ratio.